Associations between dyslexia and children's mental health: Findings from a follow-up study in China. (June 2023) - Xiao, Pei; Zhu, Kaiheng; Feng, Yanan; Jiang, Qi; Xiang, Zhen; Zhang, Quan; Wu, Xufang; Fan, Yixi; Zou, Li; Xiao, Han; Song, Ranran
Highlights: Longitudinal data confirm that dyslexia is positively associated with stress and depressive symptoms in children, and the higher the DCCC scores, the more severe their symptoms of stress, anxiety, and depression were. The emotional symptoms can persist among dyslexic children. Measures should be taken to improve not only the reading ability but also the mental health of dyslexic children. Abstract: Dyslexia is a common learning difficulty that can lead to adverse health outcomes and socioeconomic difficulties. Evidence from longitudinal studies on the association between dyslexia and psychological symptoms in children is limited. Moreover, the psychological trends of children with dyslexia are unclear. In this study, we enrolled 2, 056 students in Grades 2 to 5, including 61 dyslexic children, who participated in three mental health surveys and dyslexia screening. All the children were surveyed for symptoms of stress, anxiety and depression. We used generalized estimating equation models to estimate changes in psychological symptoms of children with dyslexia over time and the association between dyslexia and psychological symptoms. The results showed that dyslexia was associated with stress and depressive symptoms in children in both crude (β = 3.27, 95% confidence interval [CI] [1.89∼4.65], β=1.20, 95%CI: [0.45∼1.94], respectively) and adjusted models (β = 3.32, 95%CI: [1.87∼4.77], β=1.31, 95%CI: [0.52∼2.10], respectively). In addition, we found no significant differences in the emotional status of dyslexic children in either survey. Dyslexic children are at risk for mental health issues, and persistent emotional symptoms. Therefore, interventions regarding not only reading ability but also psychological conditions should be pursued.